On the use of code mobility mechanisms in real-time systems - Ferreira, Luís (2011)
Applications with soft real-time requirements can benefit from code mobility mechanisms, as long as those mechanisms support the timing and Quality of Service requirements of applications. In this paper, a generic model for code mobility mechanisms is presented. The proposed model gives system designers the necessary tools to perform a statistical timing analysis on the execution of the mobility mechanisms that can be used to determine the impact of code mobility in distributed real-time applications.